The application of the teaching methods of Opher Brayer in the compositions of jazz pianist Yaron Herman : developing a portfolio of original compositions based upon these concepts : a thesis submitted to Massey University and Victoria University of Wellington in fulfilment of the requirements for the degree of Master of Music Performance, New Zealand School of Music - Brown, Alan (Massey University, 2013)
Yaron Herman is a talented and influential Israeli-born jazz musician, currently residing in Paris. At the age of 31, he has released six albums, the first when he was 21. What is more remarkable is that he only started learning the piano at the age of 16 (following a sports injury that curtailed his basketball career dreams), under the tutelage of Opher Brayer, who used a combination of philosophy, mathematics and psychology. The intent of this research is to firstly, identify and understand the key concepts of Brayer’s methods as applied by Yaron Herman, and secondly, develop a portfolio of compositions utilising these principles. A recital of these tunes will then be presented.
Hard copy of thesis accompanied by DVD of recital footage
Keywords: Joseph Schillinger; Yaron Herman; Jazz musicians; Composition (Music); Musical intervals and scales; Jazz; Performance